New genetic biomarkers predicting azathioprine blood concentrations in combination therapy with 5-aminosalicylic acid. - Kazuhiko Uchiyama (Public Library of Science (PLoS), 2014)
Background and aims Azathioprine (AZA) is widely used for the treatment of inflammatory bowel disease (IBD) patients. AZA is catabolized by thiopurine S-methyltransferase (TPMT), which exhibits genetic polymorphisms. It has also been reported that 5-aminosalicylic acid (5-ASA) inhibits TPMT activity, and that increased 6-thioguanine nucleotide (6-TGN, a metabolite of AZA) blood concentrations result in an increased number of ADRs. In this study, single nucleotide polymorphisms (SNPs) related to differential gene expression affecting AZA drug metabolism in combination therapy with 5-ASA were examined. Methods To identify genetic biomarkers for the prediction of 6-TGN blood concentration, ExpressGenotyping analysis was used. ExpressGenotyping analysis is able to detect critical pharmacogenetic SNPs by analyzing drug-induced expression allelic imbalance (EAI) of premature RNA in HapMap lymphocytes. We collected blood samples on 38 patients with inflammatory bowel disease treated with AZA and corroboration of the obtained SNPs was attempted in clinical samples. Results A large number of SNPs with AZA/5-ASA-induced EAI within the investigated HapMap lymphocytes was identified by ExpressGenotyping analysis. The respective SNPs were analyzed in IBD patients' blood samples. Among these SNPs, several that have not yet been described to be induced by AZA/5-ASA were found. SNPs within SLC38A9 showed a particular correlation with patients' 6-TGN blood concentrations. Conclusions Based on these results, ExpressGenotyping analysis and genotyping of patients appears to be a useful way to identify inter-individual differences in drug responses and ADRs to AZA/5-ASA. This study provides helpful information on genetic biomarkers for optimized AZA/5-ASA treatment of IBD patients.